1998
DOI: 10.1021/bi9717946
|View full text |Cite
|
Sign up to set email alerts
|

Slow Cooperative Folding of a Small Globular Protein HPr

Abstract: The folding of an 85-residue protein, the histidine-containing phosphocarrier protein HPr, has been studied using a variety of techniques including DSC, CD, ANS fluorescence, and NMR spectroscopy. In both kinetic and equilibrium experiments the unfolding of HPr can be adequately described as a two-state process which does not involve the accumulation of intermediates. Thermodynamic characterization of the native and the transition states has been achieved from both equilibrium and kinetic experiments. The heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
85
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 58 publications
15
85
0
Order By: Relevance
“…This finding is again in good agreement with the dependency of the refolding rates on GdnHCl concentration observed for the WT protein refolded in the presence of ANS (13). This result further supports the assumption that the slow phase involves a local rearrangement of tertiary structure and as such is not very sensitive to changes in the denaturant concentration.…”
Section: Kinetic Folding and Unfolding Measurements (I) Refolding Ofsupporting
confidence: 89%
See 3 more Smart Citations
“…This finding is again in good agreement with the dependency of the refolding rates on GdnHCl concentration observed for the WT protein refolded in the presence of ANS (13). This result further supports the assumption that the slow phase involves a local rearrangement of tertiary structure and as such is not very sensitive to changes in the denaturant concentration.…”
Section: Kinetic Folding and Unfolding Measurements (I) Refolding Ofsupporting
confidence: 89%
“…Kinetic refolding studies of F2W, F29W, and F48W showed a major single phase, independent of the probe used (CD, fluorescence, and fluorescence anisotropy) and similar to that of the wild-type protein. In contrast, F22W showed two phases in the fluorescence experiments corresponding to the two phases previously observed in ANS binding studies of the wild-type protein [Van Nuland et al (1998) Biochemistry 37,[622][623][624][625][626][627][628][629][630][631][632][633][634][635][636][637]. Residue 22 was found from NMR studies to be part of the binding interface on HPr for ANS.…”
mentioning
confidence: 46%
See 2 more Smart Citations
“…Previous investigations on the folding mechanisms of a few knotted proteins established that these proteins have complex multistep folding pathways with slow kinetics rather than the simple two-state mechanisms that are commonly seen for small, fast-folding, single-domain proteins (6)(7)(8)(9)(10)(11). Despite experimental and computational work over the last 10 years (12)(13)(14)(15)(16)(17), the folding mechanisms of knotted proteins remain poorly understood compared with those described for small model systems that have been studied in great detail (18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%